Case Report: Identification and functional characterization of a novel heterozygous splice-donor (c.647+1G>A) site mutation in the SPTB gene that causes hereditary spherocytosis with hemolytic anemia - Cao, Ke; Luo, Xiaojuan; Liu, Lianlian; Mao, Xiaoning; Liu, Ruping; Chen, Yunsheng; Banerjee, Santasree (Frontiers in Genetics, 2025)
ObjectiveHereditary spherocytosis (HS) is an inherited disorder characterized by spherical erythrocytes and abnormalities of several erythrocyte membrane proteins with extreme genotypic and phenotypic heterogeneity. HS patients were clinically diagnosed by the presence of spherical erythrocytes on the peripheral blood smear, hemolytic anemia, jaundice, and splenomegaly, with or without cholelithiasis or gallstones. To date, mutations of five genes (ANK1, EPB42, SLC4A1, SPTA1, and SPTB) have been reported to be associated with different subtypes of HS. Germline mutations of the SPTB gene cause autosomal dominant HS (Spherocytosis 2, SPH2), the rarest subtype of HS.MethodsIn this study, we investigated a 10-year-old Chinese girl clinically diagnosed with HS and neonatal hemolytic anemia. The proband’s mother was also identified with HS and hemolytic anemia, but the proband’s father was phenotypically normal. We performed a standard G-banding karyotype to identify structural abnormalities of chromosomes in this proband. Then, we performed whole-exome sequencing and Sanger sequencing to identify the disease-causing variants in this proband. Finally, we functionally characterized the identified novel variant by performing reverse transcription polymerase chain reaction, cDNA sequencing, quantitative real-time polymerase chain reaction (PCR), and Western blot.ResultsWhole exome sequencing identified a heterozygous novel splice-donor-site (c.647 + 1G>A) mutation in the SPTB gene in the proband. Sanger sequencing confirmed that the proband inherited this mutation from her mother, while her father was devoid of it. Reverse transcription polymerase chain reaction and cDNA sequencing showed that this novel splice-donor-site (c.647 + 1G>A) mutation causes abolition of the wild-type splice donor site, which leads to the aberrant splicing of SPTB mRNA, followed by the formation of an alternative transcript with complete loss of exon 5. The relative expression of mutated SPTB mRNA was significantly reduced in the proband and her mother compared with her father, showing normal expression of wild-type SPTB mRNA.ConclusionOur present study highlighted the significance of whole-exome sequencing as the most promising path to genetic molecular diagnosis for patients with HS.